Arv1; a “Mover and Shaker” of Subcellular Lipids - J. Jose Corbalan; Karla K. Frietze; Joseph Nickels; Stephen L. Sturley (Contact)
The composition of eukaryotic membranes reflects a varied but precise amalgam of lipids. The genetic underpinning of how such diversity is achieved or maintained is surprisingly obscure, despite its clear metabolic and pathophysiological impact. The Arv1 protein is represented in all eukaryotes and was initially identified in the model eukaryote Sacccharomyces cerevisiae as a candidate transporter of lipids from the endoplasmic reticulum. Human Arv1 has been shown to directly bind cholesterol and fatty acid affinity probes. Murine in vivo studies point to a role for ARV1 in regulating obesity, glucose tolerance, insulin sensitivity and brain function. Multiple human ARV1 variants have been associated with epileptic encephalopathy, cerebellar ataxia, and severe intellectual deficits. We hypothesize that Arv1 acts as an energy independent, lipid scramblase at the endoplasmic reticulum thereby modulating membrane lipid asymmetry and thus the trafficking of sterols and the substituents of glycosyl-phosphatidylinositol and sphingolipid biosynthesis.